«OUR FRIEND – CERN» PROJECT – THREE YEARS OF SEARCH AND ACHIEVEMENTS - Yurov, O. (Physical and Mathematical Education, 2021)
Problem formulation. The National Center "Small Academy of Sciences of Ukraine" initiated the project "Our Friend - CERN", aimed at creating a system to support the effective use of nuclear research by teachers in Ukraine (CERN, Geneva, Switzerland). To create such a system requires knowledge of the factors of effectiveness of the process of knowledge transfer and their consideration in educational practice, providing quality physical and mathematical education and increasing the interest of young people in it and science in general.Materials and methods. Study of requests, evaluations and proposals of project participants through an interactive survey followed by processing of the obtained data using the Delphi method. Based on the results of generalization and analysis of the obtained data, conclusions and recommendations are formulated.Results. A study of the main achievements of training at CERN teachers-students of schools in 2018 and 2019. and students-students of schools in 2017 and 2018. In the conditions of the quarantine caused by COVID-19 in 2020, a package of compensatory measures was formed, webinars were developed, in the period April -2020 - February-2021 19 online classes were held, including 6 webinars-bridges of CERN-Ukraine. Videos of the mentioned webinars have been published on the Internet.Conclusions. The system of support and dissemination of knowledge obtained at CERN created in Ukraine is one of the effective factors of Ukraine's cooperation with CERN and has proved its viability under quarantine. The system has earned approval among teachers and students.
Keywords: Our Friend-CERN Project; CERN All-Ukrainian Club of Honorary Ambassadors of Science in Ukraine; CERN